Extra Gastric Hematological Display of Helicobacter Pylori Infection - Kashif, Zertaj; Fateen, Tooba; Shafqat, Faiza; Ali, Sehar Shamshad; Latif, Saadia; Parveen, Saadat; Warriach, Sonia Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To scrutinize extra gastric associations of Helicobacter Pylori (H Pylori) infection with disorders those come under hematology domain. Design: Descriptive cross sectional Place and duration: Histopathology and hematology department of Bakhtawar Amin Medical & Dental College and Trust hospital, Multan from Jan 2021 to Dec 2021 Material and methods: Complete blood count (CBC) and peripheral blood microscopic examination were done in every histopathologically approved H Pylori positive patient to record hemoglobin (Hb %), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and platelet count. Serum Iron, serum ferritin, serum Vitamin B 12 and folic acid levels were done in suspected cases only. Patients with low platelet count were checked in detail for immune thrombocytopenic purpura (ITP). The CBC samples were taken twice once at the time of delivery of histopathology report and second time after treatment of H Pylori infection to check reversal of counts and peripheral blood changes for authentication of H Pylori association with these blood changes. The test results along with the essential details like age, gender, nutritional history, previous medical history esp. related to these disorders and menstrual history in females were recorded on excel sheet and the proportions of all the variables were calculated to extract appropriate tables and figures. Results: Out of total 132 gastric biopsies received in Histopathology department Helicobacter Pylori prevalence noted to be 78.8 %. Eighty three (79.8 %) out of 104 H Pylori positive cases revealed extra gastric hematological manifestations and in 59 (56.7 %) of these patients the blood indices along with peripheral blood picture returned to normal on H Pylori eradication. Conclusion: A large number of H Pylori positive patients displayed hematological manifestations that reverted to normal on taking H Pylori treatment. H Pylori should be kept in mind especially dealing cases of unexplained iron deficiency, vitamin B12 anemia and Immune thrombocytopenia.